Tourism Gentrification and the Resignification of Cultural Heritage in Postmodern Urban Spaces in Latin America - Javier Benedí-Artigas; Victoria Sanagustín-Fons; J. Antonio Moseñe-Fierro (Societies)
This article presents a social and historical analysis of Barranco district in Lima, Peru, examining its evolution as a postmodern tourism destination. Through documentary analysis of historical records, guidebooks, press articles, and novels, we investigate the significant social milestones along history with cultural, and economic impacts on tourism development in Barranco. The research employs a methodology to identify key elements that have shaped Barranco’s trajectory from a fishing settlement to a bohemian district in a lively city and finally to its status as a “hipster” neighbourhood. Drawing on postmodern tourism theory and Hawley’s socioeconomic development theory, we argue that Barranco represents a distinctive case of how cultural capital transforms and resignifies tourism spaces through complex identity processes. Findings reveal that Barranco’s development follows three clear phases: rural settlement (until the 19th century), seaside resort (mid-19th century to 1940s–60s), and urban district with postmodern tourism appeal (1990s onward). The study concludes that while Barranco’s bohemian and artistic identity has become a distinctive tourism asset, the district faces gentrification challenges that threat its sociocultural diversity and authenticity. This research contributes to understanding how postmodern tourism influences territorial identity transformation and illuminates the social, historical, and economic forces that shape distinctive urban tourism destinations.